Bone marrow CD34+ progenitor cells may harbour HIV-DNA even in successfully treated patients. (March 2015) - Bordoni, V.; Bibas, M.; Abbate, I.; Viola, D.; Rozera, G.; Agrati, C.; Rinaldi, A.; Amendola, A.; Ammassari, A.; Capobianchi, M.R.; Martini, F.
Abstract: The issue about bone marrow hematopoietic progenitor cells harbouring HIV-DNA in infected patients is still under scrutiny. We studied nine HIV-infected individuals undergoing bone marrow aspiration for diagnostic purposes. In all patients, even in those receiving successful antiretroviral therapy for several years, HIV-DNA was detected in purified CD34+ lineage-bone marrow progenitor cells. This finding, although not conclusive due to the low number of patients examined, adds further evidence that current treatment strategies may be insufficient to resolve latent infection in bone marrow CD34+ hematopoietic progenitor cells.